Unveiling the role of interleukin-6 in pancreatic cancer occurrence and progression - Song, Meihui; Tang, Ying; Cao, Kaimei; Qi, Ling; Xie, Keping (Frontiers in Endocrinology, 2024)
Pancreatic cancer is difficult to diagnose early and progresses rapidly. Researchers have found that a cytokine called Interleukin-6 (IL-6) is involved in the entire course of pancreatic cancer, promoting its occurrence and development. From the earliest stages of pancreatic intraepithelial neoplasia to the invasion and metastasis of pancreatic cancer cells and the appearance of tumor cachexia, IL-6 drives oncogenic signal transduction pathways and immune escape that accelerate disease progression. IL-6 is considered a biomarker for pancreatic cancer diagnosis and prognosis, as well as a potential target for treatment. IL-6 antibodies are currently being explored as a hot topic in oncology. This article aims to systematically explain how IL-6 induces the deterioration of normal pancreatic cells, with the goal of finding a breakthrough in pancreatic cancer diagnosis and treatment.